PRAKTEK SAMPLING AUDITOR DALAM PELAKSANAAN AUDIT - Rasin Tarigan; Heru Satyanugraha (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2005)
This study examines audit sampling practices by Indonesian auditors. Data for the study were collected from 105 auditors from public accounting firms in Jakarta. Analysis was done quantitatively to reveal that auditors do sampling in doing audit. Results also show that statistical sampling methods are used more often than non-statistical sampling methods. In using statistical sampling, simple random sampling is the technique used most often, while haphazard sampling is the technique used most often for the non-statistical sampling method. Most auditors received training of sampling while they are at college as well as while working. Auditors normally take precaution to manage bias while using non-statistical method.